2012
DOI: 10.1002/adma.201103800
|View full text |Cite
|
Sign up to set email alerts
|

From Monolayer to Multilayer N‐Channel Polymeric Field‐Effect Transistors with Precise Conformational Order

Abstract: Monolayer field-effect transistors based on a high-mobility n-type polymer are demonstrated. The accurate control of the long-range order by Langmuir-Schäfer (LS) deposition yields dense polymer packing exhibiting good injection properties, relevant current on/off ratio and carrier mobility in a staggered configuration. Layer-by-layer LS film transistors of increasing thickness are fabricated and their performance compared to those of spin-coated films.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
137
1
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 115 publications
(147 citation statements)
references
References 49 publications
8
137
1
1
Order By: Relevance
“…This particular morphology allows good electron transport in both organic diodes and field-effect transistors (OFETs), with high in-plane mobilities of ∼0.1-0.6 cm 2 ·V -1 ·s -1 even in the presence of a substantial degree of disorder (11). However, film morphologies with predominantly edge-on oriented polymer chains were observed to yield lower performance in both diodes and top-gated OFETs because of the reduced out-of-plane mobility and larger injection barrier (16)(17)(18)(19). In a recent publication, Neher and coworkers also showed that this polymer has a strong tendency to aggregate, which greatly affects the bulk optical and electrical properties (20,21).…”
mentioning
confidence: 99%
“…This particular morphology allows good electron transport in both organic diodes and field-effect transistors (OFETs), with high in-plane mobilities of ∼0.1-0.6 cm 2 ·V -1 ·s -1 even in the presence of a substantial degree of disorder (11). However, film morphologies with predominantly edge-on oriented polymer chains were observed to yield lower performance in both diodes and top-gated OFETs because of the reduced out-of-plane mobility and larger injection barrier (16)(17)(18)(19). In a recent publication, Neher and coworkers also showed that this polymer has a strong tendency to aggregate, which greatly affects the bulk optical and electrical properties (20,21).…”
mentioning
confidence: 99%
“…The hole mobility of the monolayer FET can reach 0.014 cm 2 V −1 s −1 with an average µ h of 0.008 cm 2 V −1 s −1 , which is among the highest charge mobility reported for FETs with ultrathin films prepared with Langmuir technique. [29][30][31][32][33][34][35] Moreover, the monolayer FET exhibits relatively high I on/off (10 4 -10 6 ). µ h increased to 0.015 and 0.02 cm 2 V −1 s −1 for FETs with bilayer and threelayer ultrathin films, respectively.…”
Section: Thin Film Field-effect Transistorsmentioning
confidence: 99%
“…This can be attributed to the fact that PDPP3T1 entails amphiphilic side chains. According to previous studies, [35,38] the hydrophilic part (TEEG chains) of PDPP3T1 is assumed to be located in the water subphase, while the hydrophobic part of the polymer is expected to adopt a perpendicular orientation with respect to the water surface.…”
Section: Formation Of Monolayer Thin Film At Air-water Interfacementioning
confidence: 99%
See 2 more Smart Citations